Asymptotic properties of count models for automobile insurance claims in emerging markets: Insight from Tanzania - Laurent L. Lulu; Ramkumar T. Balan; Peter Josephat Kirigiti (Next Research, 2026)

A Review on the Biodegradation of Kraft Lignin Wastes to Minimize Pollution Load in Paper Industry - Shrinidhi Sureshbabu; Ashmitha Kalairaj; Swethashree Rajendran; V. Ramkumar; Rames C. Panda; T. Senthilvelan (Water, Air, & Soil Pollution, 2026)

Spatiotemporal patterns of jellyfish distribution along the Maharashtra coast, India - M.R. Ashpel Mano; S. Ramkumar; Asha T. Landge; S. Abuthagir Iburahim; K. Nikhil; Sonam Angmo; Karankumar Ramteke; B.B. Nayak; Suryapraba (Regional Studies in Marine Science, 2026)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Nanoparticle assorted biofuels production from biowastes through transesterification - T. Sathish; R. Saravanan; M. Rajasimman; Ayman A. Ghfar; Vanaraj Ramkumar (Fuel, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Simultaneous detection of medium-scale traveling ionospheric disturbances and ionospheric plasma irregularities over Srinagar, J&K, India - Aashiq Hussain Bhat; Bilal Ahmad Ganaie; T. K. Ramkumar; P. Pavan Chaitanya; Manzoor A. Malik (Acta Geophysica, 2021)

Transport Analysis of Engineered Liver Tissue Fabricated Using a Capsule-Based, Modular Approach - Ramkumar T. Annamalai; Howard W. T. Matthew (Annals of Biomedical Engineering, 2019)

Identification of saline water intrusion in part of Cauvery deltaic region, Tamil Nadu, Southern India: using GIS and VES methods - G. Gnanachandrasamy; T. Ramkumar; S. Venkatramanan; S. Y. Chung; S. Vasudevan (Marine Geophysical Research, 2016)

Environmental monitoring and assessment of heavy metals in surface sediments at Coleroon River Estuary in Tamil Nadu, India - S. Venkatramanan; S. Y. Chung; T. Ramkumar; S. Selvam (Environmental Monitoring and Assessment, 2015)

Comprehensive studies of hydrogeochemical processes and quality status of groundwater with tools of cluster, grouping analysis, and fuzzy set method using GIS platform: a case study of Dalcheon in Ulsan City, Korea - S. Venkatramanan; S. Y. Chung; R. Rajesh; S. Y. Lee; T. Ramkumar; M. V. Prasanna (Environmental Science and Pollution Research, 2015)

Influence of hydrogeochemical processes and assessment of suitability for groundwater uses in Busan City, Korea - S. Y. Chung; S. Venkatramanan; T. H. Kim; D. S. Kim; T. Ramkumar (Environment, Development and Sustainability, 2015)

An assessment of selected hydrochemical parameter trend of the Nakdong River water in South Korea, using time series analyses and PCA - S. Y. Chung; S. Venkatramanan; N. Park; R. Rajesh; T. Ramkumar; B. W. Kim (Environmental Monitoring and Assessment, 2015)

Identification and characterization of tsunami deposits off southeast coast of India from the 2004 Indian Ocean tsunami: Rock magnetic and geochemical approach - S Veerasingam; R Venkatachalapathy; N Basavaiah; T Ramkumar; S Venkatramanan; K Deenadayalan (Journal of Earth System Science, 2014)

Heavy metal distribution in surface sediments of the Tirumalairajan river estuary and the surrounding coastal area, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; S. Vasudevan (Arabian Journal of Geosciences, 2014)

Speciation of selected heavy metals geochemistry in surface sediments from Tirumalairajan river estuary, east coast of India - S. Venkatramanan; T. Ramkumar; I. Anithamary; M. P. Jonathan (Environmental Monitoring and Assessment, 2013)

Genetic structure and diversity of India hybrid tea - S. N. Raina; P. S. Ahuja; R. K. Sharma; S. C. Das; P. Bhardwaj; R. Negi; V. Sharma; S. S. Singh; R. K. Sud; R. K. Kalia; V. Pandey; J. Banik; et al. (Genetic Resources and Crop Evolution, 2012)

Stable isotope analyses of belemnites from the Kachchh Basin, western India: paleoclimatic implications for the Middle to Late Jurassic transition - Matthias Alberti; Franz T. Fürsich; Dhirendra K. Pandey; Mu. Ramkumar (Facies, 2012)

Environmental magnetic and geochemical characteristics of Chennai coastal sediments, Bay of Bengal, India - R VENKATACHALAPATHY; S VEERASINGAM; N BASAVAIAH; T RAMKUMAR; K DEENADAYALAN (Journal of Earth System Science, 2011)

Alterations in inheritance pattern and level of cytosine DNA methylation, and their relationship with heterosis in rice - K. Sakthivel; K. Girishkumar; G. Ramkumar; V. V. Shenoy; S. T. Kajjidoni; P. M. Salimath (Euphytica, 2010)

Petroleum Hydrocarbon Concentrations in Marine Sediments Along Chennai Coast, Bay of Bengal, India - R. Venkatachalapathy; S. Veerasingam; T. Ramkumar (Bulletin of Environmental Contamination and Toxicology, 2010)

Tolerance of Bt corn (MON 810) to maize stem borer, Chilo partellus (Lepidoptera: Pyralidae) - Ramkumar; K. C. Ravi; Farah Deeba; J. N. Nandi; K. S. Mohan; T. M. Manjunath (Plant Cell Reports, 2005)